A numerical analysis on double acting pneumatic telescopic cylinder motion characteristics - Din, Abdul Talib; Rahimi, Roslina Aida (2010)
This paper presents the design and development of a mathematical model of dynamic motion of pneumatic telescopic cylinder. The design analysis carried out is focused and based mainly on identifying the characteristics of the pneumatic cylinder using force-feedback control system. A conceptual model was made and the limitations were identified and further studied on nonlinear behavior and the solutions to improve its characteristics were sought in the process of designing and developing the telescopic cylinder. The control system contained combination of proportional and on-off valve in controlling the telescopic cylinder movement. The determination of the displacement of each stage of the telescopic cylinder, velocity and acceleration were optimized using multi-order PI controller. Simulation studies were performed using Matlab Simulink to prove the dynamic mathematical modeling of the cylinder. During the last stage of the research, a scale down model of the telescopic cylinder was fabricated incorporating all design aspects derived from the theoretical and simulation analysis. An experimental study was conducted on the scale down cylinder in order to validate the data obtained. The validated data shall be used in the design of the full scale of the telescopic cylinder.